2023
DOI: 10.1002/adom.202300499
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Resonance Tailoring of Individual Split‐Ring Resonators with Phase‐Change Materials by Locally Changing the Dielectric Surrounding of the Antenna Hotspots

Abstract: For miniaturized active metasurfaces, resonance tuning of nanoantennas is a key ingredient. Phase‐change materials (PCMs) have been established as prime candidates for non‐volatile resonance tuning enabled by a change in the refractive index around nanoantennas. Conventionally, this tuning is induced by annealing the entire sample equally and does not allow changes on a meta‐atom level. Recently, it is demonstrated that individual rodantenna resonances can be adjusted by addressing each meta‐atom locally with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
(85 reference statements)
0
4
1
Order By: Relevance
“…Figure 1A): If the entire slit is covered by crystalline GST, only the crystallization depth influences the resonance position of the nanoantennas. This is drastically different from the resonance tuning mechanism previously observed for the conventional antenna structure of nanorods and split-ring resonators: 24,28 There, it was found that the resonance tuning is invariably influenced by both the spot size and the crystallization depth simultaneously because the fields of the antenna structures extend outward from the antenna ends (see Supplementary Note 1).…”
Section: Resultscontrasting
confidence: 72%
See 3 more Smart Citations
“…Figure 1A): If the entire slit is covered by crystalline GST, only the crystallization depth influences the resonance position of the nanoantennas. This is drastically different from the resonance tuning mechanism previously observed for the conventional antenna structure of nanorods and split-ring resonators: 24,28 There, it was found that the resonance tuning is invariably influenced by both the spot size and the crystallization depth simultaneously because the fields of the antenna structures extend outward from the antenna ends (see Supplementary Note 1).…”
Section: Resultscontrasting
confidence: 72%
“…In particular, the crystallization depth plays a major role for the resonance shift. 24,28 In Figure 2B, four different slit antenna arrays locally addressed with crystallization pulses of varied pulse duration, and the corresponding measured reflectance spectra are visualized. At first, the slits were covered by amorphous GST.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, both phases show a large contrast in the refractive index, caused by a change in chemical bonding. In the amorphous phase, the atoms are covalently bonded, but in the crystalline phase a new bonding type occurs which is called metavalent 27 31 . The reversible phase change can be induced by locally heating the PCM with electrical or optical pulses.…”
Section: Introductionmentioning
confidence: 99%